Occlusion training during specific futsal training improves aspects of physiological and physical performance - Amani-Shalamzari, S.; Sarikhani, A.; Paton, C.; Rajabi, H.; Bayati, M.; Nikolaidis, P. T.; Knechtle, B. (Journal of Sports Science & Medicine, 2020)
This study aimed to examine the effects of lower limb blood flow restriction (BFR) performed during 3-a-side futsal game training on aerobic and anaerobic performance of futsal players. Twelve male futsal players were randomized into two groups (n = 6); both groups performed ten sessions of the 3-a-side game every other day in half of a futsal court; but one group trained under BFR conditions. Pneumatic cuffs used for the BFR group were inflated to 110% leg systolic blood pressure and increased by 10% after each two completed sessions. Before and after the training sessions subjects completed a series of tests to assess aerobic and anaerobic performances along with changes in blood lactate and anabolic and catabolic hormones. All aerobic and anaerobic performance variables improved in both group after training, however improvements in mean power (12.2%, p = 0.03), run time to fatigue (TTF), (7.1%, p = 0.02) and running economy (RE), (-22.7%, p = 0.01) were significantly greater in the BFR group. There were also significant increases in growth hormone (p = 0.01), testosterone to cortisol ratio at first session (p = 0.01) and rate of lactate removal (p = 0.01) at last session in the BFR group compared to the non-BFR group. Small-sided game (SSG) training with the addition of BFR because of accumulated metabolites and hormonal changed leads to substantially greater increases in performance than SSGs training alone.